Surface temperatures and vacation burns occurring during grinding of cemented gears with two dished wheels on different parts of the machined involute profile - Tonkonogyi, Volodymyr; Yakymov, Oleksiy; Bovnegra, Liubov; Nоvikоv, Fеdir (Національний технічний університет "Харківський політехнічний інститут", 2023)
To increase grinding productivity with the provision of specified physical and mechanical properties of the surface layer of the surface layer of the processed part it is necessary to know the temperature on the surface of the workpiece, since its value depends on the depth of the defective surface layer. In the work theoretically justified the difference of surface temperatures in the initial (at the base), in the middle (on the dividing circle) and final (at the top) points of involute profile of the gear tooth when grinding with two disc wheels on the zero scheme. The difference in temperature at different points of the processed tooth profile is justified by the fact that at different parts of the trajectory of the movement of the heat source acts a different number of thermal pulses. These pulses have different duration and time intervals between the actions of these pulses in different points of the involute profile are also different. The number of thermal actions on a fixed point of the machined profile depends on the length of the heat source, and the duration of heating of the surface at this point is determined by the width of the heat source. The duration of cooling depends on the location of the point on the involute profile. Mathematical models have been developed to calculate the temperatures at different parts of the trajectory of the rolling path of a disc grinding wheel on the tooth being machined. Each of these formulas contains two sums. The first sum determines the temperature increase at a fixed point of the tooth profile under repeated exposure to thermal pulses during the forward stroke, and the second sum - during the reverse stroke. Mathematical models are based on the principle of superposition of thermal fields. It is found that the temperature in the middle part of the tooth is 40% less than at the tooth apex and 20% less than at the tooth base. The engineering method of distribution of the total allowance by passes at multi-pass gear grinding with two dished wheels according to the zero scheme has been developed. The method is based on the experimental dependence of the depth of the defect layer on the depth of cutting, which has a linear character. In the work, calculations were made on the allowance distribution in the initial, middle and final points of the involute tooth profile. The calculations showed that in order to prevent burns on the final machined surface, grinding in different parts of the machined profile should be performed with a different number of passes. The smallest number of passes on the separating circle, and the largest - on the top of the tooth. The proposed methodology of distribution of allowances by passes can be used at the stage of design of gear grinding operation (for optimization of modes) and at the stage of machining (for diagnostics of the operation). It is theoretically substantiated that calculations of allowance distribution by passes should be made only for the tooth head. To increase grinding productivity with provision of the specified physical and mechanical properties of the surface layer of the processed part it is necessary to know the temperature on the surface of the workpiece, as its value depends on the depth of the defective surface layer. In the work theoretically justified the difference in surface temperatures in the initial (at the base), in the middle (on the dividing circle) and final (at the top) points of involute profile of the gear tooth when grinding with two disk wheels on the zero scheme. The difference in temperature at different points of the processed tooth profile is justified by the fact that at different parts of the trajectory of the heat source acts a different number of thermal pulses. These pulses have different duration and time intervals between the actions of these pulses in different points of the involute profile are also different. The number of thermal actions on a fixed point of the machined profile depends on the length of the heat source, and the duration of heating of the surface at this point is determined by the width of the heat source. The duration of cooling depends on the location of the point on the involute profile. Mathematical models have been developed to calculate the temperatures at various parts of the rolling path of a dished grinding wheel on a machined tooth. Each of these formulas contains two sums.

Для підвищення продуктивності шліфування із забезпеченням заданих фізико-механічних властивостей поверхневого шару оброблюваної деталі необхідно знати температуру на поверхні заготовки, оскільки від її величини залежить глибина дефектного поверхневого шару. У роботі теоретично обґрунтовано відмінність поверхневих температур у початковій (біля основи), у середній (на ділильному колі) і кінцевій (біля вершини) точках евольвентного профілю зуба шестірні при шліфуванні двома тарілчастими кругами за нульовою схемою. Відмінність температур у різних точках оброблюваного профілю обґрунтовується тим, що на різних ділянках траєкторії переміщення теплового джерела діє різна кількість теплових імпульсів. Ці імпульси мають різну тривалість та проміжки часу між діями цих імпульсів у різних точках евольвентного профілю теж різні. Кількість теплових дій на фіксовану точку оброблюваного профілю залежить від довжини теплового джерела, а тривалість нагрівання поверхні в цій точці визначається шириною теплового джерела. Тривалість охолодження залежить від місця розташування точки на евольвентному профілі. Розроблено математичні моделі для розрахунку температур на різних ділянках траєкторії обкатування тарілчастого шліфувального круга по оброблюваному зубу. Кожна з цих формул містить дві суми. Перша сума визначає збільшення температури у фіксованій точці профілю зуба при багаторазовій дії на неї теплових імпульсів при прямих ходах, а друга сума – при зворотних ходах. Математичні моделі ґрунтуються на принципі суперпозиції теплових полів. Встановлено, що температура в середній частині зуба на 40% менше, ніж у вершини зуба і на 20% менше, ніж у його основи. Розроблено інженерну методику розподілу загального припуску за проходами для багатопрохідного зубошліфування двома тарілчастими кругами за нульовою схемою. Методика ґрунтується на експериментальній залежності глибини дефектного шару від глибини різання, що має лінійний характер. У роботі виконано розрахунки з розподілу припуску в початковій, середній та кінцевій точках евольвентного профілю зуба. Розрахунки показали, що для запобігання появі припікань на остаточно-обробленій поверхні шліфування на різних ділянках оброблюваного профілю повинно здійснюватися з різним числом проходів. Найменша кількість проходів на ділильному колі, а найбільша – біля вершини зуба. Запропонована методика розподілу припуску за проходами може бути використана на етапі проектування операції зубошліфування (для оптимізації режимів) і на етапі механічної обробки (при діагностиці операції). Теоретично обґрунтовано, що розрахунки з розподілу припуску за проходами слід здійснювати тільки на головці зуба.
Поверхневі температури і припікання відпустки, виникаючі під час шліфування цементуючих зубчатих коліс двома тарільчастими кругами, на різних ділянках оброблюваного евольвентного профілю
Keywords: dished wheels; zero scheme; tempering burns; multi-pass grinding; тарілчасті круги; нульова схема; припікання відпалу; багатопрохідне шліфування